Analisis Urban Heat Island Kota Samarinda Menggunakan Citra Landsat 9 Pada Musim Kemarau Tahun 2025 - Romansah Wumu; Nia Kurniadin; F. V. Astrolabe Sian Prasetya; Shabri Indra Suryalfihra; Dawamul Arifin (Geomatics Technology Study Program, Politeknik Pertanian Negeri Samarinda, 2026)
Urban Heat Island (UHI) is a phenomenon where urban areas exhibit significantly higher surface temperatures compared to surrounding rural regions, driven by land use transformation and reduced vegetation cover. This study analyzes the UHI phenomenon in Samarinda City, East Kalimantan, using Landsat 9 OLI-2/TIRS-2 imagery (Collection 2, Level 2) processed through Google Earth Engine (GEE). The analysis covers May–October 2025 (dry season) using a median composite of two cloud-free scenes. Land Surface Temperature (LST) was extracted using the Single-Channel Algorithm with NDVI-based emissivity correction. Spectral indices NDVI, NDBI, and MNDWI were computed to examine their relationships with LST. UHI intensity was classified into five categories based on mean ± standard deviation thresholds. Results indicate a mean LST of 36.79°C (range: 12.35–60.69°C). High and Very High UHI classes cover 131.31 km² (21.13%) of the city area, concentrated in Samarinda Kota sub-district (mean LST 45.01°C). Correlation analysis using 90 random sampling points reveals NDBI as the strongest LST predictor (r = +0.72), while NDVI shows a moderate negative correlation (r = −0.35). These findings provide spatial evidence for urban heat mitigation strategies, particularly through green space enhancement and built-up density control in high-intensity UHI zones.